Family Resources, Family Size, and Access to Financing for College Education - Behrman, Jere R.; Pollak, Robert A.; Taubman, Paul (Journal of Political Economy, 1989)
Unequal access to financing for education may be an important source of educational differences. We develop a model relating sib schooling and earnings similarities to sibship size with and without equal access and estimate it for the education of veterans, for whom the GI Bill assured equal access, and for their children, who had no such government assistance. We find an inverse relationship between sibship size and sib schooling and earnings similarities for the children, but not for the veterans; we conclude that, in the absence of equal access policies, unequal access is an important source of educational differences.